Design Sciences as Applied Sciences and the role of values: Analysis of the case of Education - Alonso Rodríguez, Ana María (Analysis. Journal of Philosophical Research, 2022)
The debate on values in science is particularly topical in the present intellectual scenario, marked by climate change, the Covid-19 pandemic and technological challenges. Accepting that science is value-laden links the methodology of science with the axiology of research and focus on the ethics of science as a facet that must also be considered in the philosophical analysis of science. This is especially clear in applied sciences.The role of values in the sciences of design as applied sciences is analysed here. Education is taken as a reference, a discipline with an undoubted ethical dimension, increasingly linked to technology, and that has barely received the attention of philosophy of science. The analysis follows several steps: (i) the different axiological load of applied science with respect to basic science is raised; (ii) the presence of values in education as a science of design is verified; (iii) the links with the axiology of research and the ethics of science are indicated; and (iv) some ethical issues related to the incorporation of technology are identified.